COMPATIBILITY OF NEWER INSECTICIDES AND FUNGICIDES AGAINST INSECT PESTS AND DISEASES OF RICE (Journal of Plant Disease Sciences, 2017)
Trial wasundertaken at Agriculture Research Station, Sakoli, Dist. Bhandara (M.S.) during 2014 to evaluate the compatibility of selected Kharif, insecticides and fungicides as tank mix as reflected by their effectiveness against major insect pests and diseases of rice under field condition.Rynaxypyr + validamycin and rynaxypyr werehighly effective against dead heart (stem borer) and white earhead (stem borer), respectively. Lowest incidence of gall midge was recorded in dinotefuran. Leaf folder incidence was low in rynaxypyr + combination fungicide (carbendazim + mancozeb). In case of plant hoppers, the treatments showed significant differences, however pest incidence was very low and there were no discernible trends in the effectiveness of treatments. Meager incidence of blast and sheath blight and moderate incidence of bacterial leaf blight was observed during 2014. Validamycin and carbendazim + mancozeb in combination Kharif, with insecticides found as effective as applied alone for management of bacterial leaf blight, blast and sheath blight. Rynaxypyr + carbendazim + mancozeb recorded highest yield (27.67 q/ha) and at par with rynaxypyr + validamycin (25.58 q/ha) and dinotefuran + carbendazim + mancozeb( 25.08 q/ha).
Keywords: Rice, compatibility, insecticides, fungicides, insect pests, diseases